Feasibility and preliminary effects of technology-assisted interventions in hybrid cardiac rehabilitation (TecHCR): A pilot randomised controlled trial. (11th May 2022) - Chong, M S; Sit, JWH; Choi, KC; Suhaimi, A; Chair, SY
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: As COVID-19 pandemic continues, using technologies within cardiac rehabilitation facilitates access to care and reduces the frequency of direct contact with vulnerable cardiac patients. We aimed to assess the feasibility of technology-assisted interventions in hybrid cardiac rehabilitation (TecHCR) and preliminarily evaluate its effects on patients with coronary heart disease (CHD). Methods: Between February 2021 to May 2021, a total of 28 patients with CHD were recruited and randomised to receive a 12-week TecHCR programme (n = 14) or a 12-week conventional, centre-based programme (n = 14). The TecHCR group received three center-based, supervised exercise training sessions. Participants were instructed to wear a fitness tracker watch for exercise self-monitoring at home environment, and the exercise data were shared through a web-based application for remote monitoring by the intervener. Participants received six audio-visual educational videos via a messaging application and a weekly video/telephone call follow-up. Self- Efficacy for Exercise (ESE), Health Promoting Lifestyle Profile II (HPLP II), Hospital Anxiety and Depression Scale (HADS), exercise capacity and cardiovascular health outcomes were assessed at baseline and at 12th week on completion of the programme. Generalised estimating equations analysis was conducted to compare the outcomes between groups. Results: Out of 28 participants (56.46±12.98 years old; 1 female), 67.9% had percutaneous coronary intervention and 28.6% had coronary bypass grafting surgery. Among 14 participants in the TecHCR group, three dropped out due to: 1) fear to attend face-to-face supervised exercise training during high daily COVID-19 cases; 2) infected with COVID-19 and 3) found a job in overseas. Eleven participants in the TecHCR group attended all video/telephone call sessions, nine participants completed 3 supervised exercise training sessions and nine participants adhered to the weekly exercise recommendations. No treatment-related adverse events were reported. TecHCR was non-inferior to conventional, centre-based program on exercise self-efficacy, exercise capacity and cardiovascular health outcomes. TecHCR group showed significantly greater improvement in health-promoting behavior when compared with the control group (p =0.013) at post-intervention. Conclusion: This pilot study demonstrated the feasibility in recruitment and implementation of TecHCR as an alternative delivery mode and could enhance health-promoting behavior among patients with CHD. Implications: The TecHCR program provides accessible interventions to patients without frequent visits to the outpatient centre. A full-scale randomised controlled trial is needed to confirm the effectiveness of TecHCR.